Exercise effects on symptoms of depression and anxiety vary by patient, clinical, and intervention characteristics in cancer survivors: results from pooled analyses of individual participant data of 26 RCTs - Kenkhuis, Marlou-Floor; Doorenbos, Meike; Mast, Isa H.; Aaronson, Neil K.; van Beurden, Marc; Bohus, Martin; Courneya, Kerry S.; Daley, Amanda J.; Galvão, Daniel A.; Goedendorp, Martine M.; van Harten, Wim H.; Hayes, Sandi C.; et al. (Supportive care in cancer, 2025)
Purpose This study aimed to investigate whether socio-demographic, clinical, and intervention-related variables moderate the effects of exercise on depression and anxiety symptoms in cancer survivors. Methods Data from 26 RCTs in the POLARIS database were analyzed using a one-step individual participant data (IPD) meta-analytic approach with linear mixed models to assess exercise effects on depression and anxiety symptoms (z-scores). Interaction terms were added to these models to explore moderators. Results are presented as betas (corresponding to Cohen’s d effect size). Results Albeit statistically significant, exercise demonstrated negligible effects on symptoms of depression (β = − 0.11; 95% CI = − 0.16; − 0.06) and anxiety (β = − 0.07; 95% CI = − 0.12; − 0.02) compared to controls. The effects of exercise interventions on depressive symptoms were larger for patients who were not living with a partner (β = − 0.23; 95% CI = − 0.35; − 0.11), had a low/medium education level (β = − 0.14; 95% CI = − 0.21; − 0.07), and who had moderate-to-severe symptoms of depression at baseline (β = − 0.30; 95% CI = − 0.43; − 0.16). Patients with moderate-to-severe symptoms of depression at baseline combined with those not living with a partner or a low/medium education level yielded the largest effect size through exercise (β = − 0.61; 95% CI = − 0.89; − 0.33 and β = − 0.37; 95% CI = − 0.57; − 0.17, respectively). Effects on anxiety symptoms were larger for patients with moderate-to-severe symptoms of anxiety at baseline (β = − 0.17; 95% CI = − 0.32; − 0.01) compared to those with no-to-mild symptoms. Sex, age, cancer type, BMI, and intervention-related variables did not moderate the exercise effects. Conclusion The findings of this study highlight the heterogeneous response to exercise interventions across various patient subgroups. Patients with moderate-to-severe anxiety or depression, those with a low/medium education, and those not living together with a partner may particularly benefit.